2020
DOI: 10.1088/1402-4896/abc647
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical analysis of steady three-dimensional flow and heat transfer of Power-Law nanofluid over a stretchable rotating disk filled with gyrotactic microorganisms

Abstract: A theoretical analysis of steady three-dimensional flow and heat transfer of Power-Law nanofluid over a stretchable rotating disk filled with gyrotactic microorganisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 49 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…They concluded that an augmentation in the value of “ Ln” will decline the heat transport rate, while increase mass, nano, and regular rates of transportation. Finally, Usman et al [ 28 ] examined the power-law non-Newtonian nanoliquid through a spinning disk occupied with gyrotactic micro-organisms. They used the shooting procedure to discuss the numerical outcomes and the effects of various physical parameters on the flow and heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that an augmentation in the value of “ Ln” will decline the heat transport rate, while increase mass, nano, and regular rates of transportation. Finally, Usman et al [ 28 ] examined the power-law non-Newtonian nanoliquid through a spinning disk occupied with gyrotactic micro-organisms. They used the shooting procedure to discuss the numerical outcomes and the effects of various physical parameters on the flow and heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…El-Dabe et al [17] examined the steady MHD flow of a power law nanofluid due to a uniform rotating infinite disk with viscous dissipation and thermal radiation using the generalized Von Karman similarity transformations. Usman et al [18] investigated the three-dimensional steady flow and heat transfer of a power law nanofluid over a stretchable rotating disk with gyrotactic microorganisms and thermal radiation using the shooting method. Usman et al [19] discussed the entropy generation for the flow of multi-walled carbon nanotubes in the ethylene glycol based fluid over a stretchable rotating disk near the stagnation point region.…”
Section: Introductionmentioning
confidence: 99%
“…Usman et al. [18] investigated the three‐dimensional steady flow and heat transfer of a power law nanofluid over a stretchable rotating disk with gyrotactic microorganisms and thermal radiation using the shooting method. Usman et al.…”
Section: Introductionmentioning
confidence: 99%
“…Usman et al 39,40 investigated the power–law and Carreau fluids in the absence of nanoparticles between two disks. Usman et al 41 also performed a theoretical analysis to study the power law in the light of nanoparticles and gyrotactic microorganisms across a single disk. Usman et al 42 further investigated the disk geometry with power–law as a lubricant and tangent hyperbolic as a bulk fluid.…”
Section: Introductionmentioning
confidence: 99%